2005
DOI: 10.1074/jbc.m503341200
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Extracellular Secreted α-Synuclein via Matrix Metalloproteinases

Abstract: Although ␣-synuclein is the main structural component of the insoluble filaments that form Lewy bodies in Parkinson disease (PD), its physiological function and exact role in neuronal death remain poorly understood. In the present study, we examined the possible functional relationship between ␣-synuclein and several forms of matrix metalloproteinases (MMPs) in the human dopaminergic neuroblastoma (SK-N-BE) cell line. When SK-N-BE cells were transiently transfected with ␣-synuclein, it was secreted into the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
213
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(226 citation statements)
references
References 52 publications
10
213
0
3
Order By: Relevance
“…However, the presence of a-Syn in the cerebrospinal fluid (CSF) of Parkinson's disease patients does support the possibility that aggregates of the protein exist outside of cell. aSyn may be released upon cell death (10) or secreted from neuronal cells, as evidenced in culture (11)(12)(13). The exocytosis of a-Syn is thought to be linked to a preferential secretion of damaged proteins from the cell (12,14).…”
Section: Alpha-synuclein and Neurotoxicitymentioning
confidence: 99%
“…However, the presence of a-Syn in the cerebrospinal fluid (CSF) of Parkinson's disease patients does support the possibility that aggregates of the protein exist outside of cell. aSyn may be released upon cell death (10) or secreted from neuronal cells, as evidenced in culture (11)(12)(13). The exocytosis of a-Syn is thought to be linked to a preferential secretion of damaged proteins from the cell (12,14).…”
Section: Alpha-synuclein and Neurotoxicitymentioning
confidence: 99%
“…α-Synuclein is also found in other regions of neurons, in astrocytes, and in oligodendroglia (6)(7)(8)(9)(10)(11). Overexpression of and mutations in α-synuclein are associated with early onset Parkinson's disease (12)(13)(14)(15) and other neurodegenerative diseases (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…To address the potential role for α-synuclein in brain 20:4n-6 uptake and metabolism, we used steady-state kinetic modeling of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]20:4n-6 metabolism in vivo coupled with studies using enzyme assays and mRNA expression of key fatty acid metabolic enzymes. These data show, for the first time, a mechanistic explanation for the impact of α-synuclein deficiency on brain lipid metabolism.…”
mentioning
confidence: 99%
“…56 Sung et al demonstrated that oxidative injury induces the cleavage of extracellular α-syn released from neuronal cells and this is eventually cleaved by MMPs. However, the cleavage of α-syn by MMP-3 further induces its aggregation, 56 lessens any likely effects on PD of cleaving extracellular α-syn by MMPs.…”
Section: Other Clearance Systems As Therapeutic Approaches Against Pdmentioning
confidence: 99%
“…Proteolytic clearance is possible using any of several proteases that have been identified to be able to cleave and degrade α-syn: these include neurosin, 55 matrix metalloproteinases (MMPs), 56 calpain, 57 cathepsin D 58 and plasmin. 59 Among them, neurosin, MMPs and plasmin have been reported to cleave and degrade extracellular α-syn.…”
Section: Other Clearance Systems As Therapeutic Approaches Against Pdmentioning
confidence: 99%